Implementasi Pembelajaran berbasis STEAM melalui Kegiatan Pembuatan Gasing di TK PGRI Purbaratu - Gusthine Almeera Irawan; Dindin Abdul Muiz Lidinillah; Qonita Qonita (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
STEAM (Science, Technology, Engineering, Arts, and Mathematics)-based learning is an approach that can be used to develop various 21st-century skills in early childhood through active and meaningful learning experiences. This study aimed to describe the implementation of STEAM-based learning through a spinning-top making activity for children aged 5–6 years at TK PGRI Purbaratu. This study employed a qualitative approach involving one classroom teacher and 15 children in Group B. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings showed that the spinning-top making activity provided opportunities for children to experience the implementation of each STEAM element through different learning activities. Science was reflected in observing, predicting, and experimenting; technology in the use of simple tools; engineering in selecting materials, constructing, testing, and improving the spinning top; arts in decorating the product; and mathematics in counting and recognizing geometric shapes. Therefore, the spinning-top making activity illustrates how a traditional play activity can meaningfully support the implementation of STEAM-based learning in early childhood education